Fraudulent financial reporting through the lens of the fraud pentagon theory - Wiwit Rica Anggraini; Ani Wilujeng Suryani (Universitas Negeri Malang, 2021)
AbstractFraud causes trillions of rupiah in losses in the business world. With the fraud pentagon lens, this study aims to examine whether pressure, opportunity, rationalization, capability and arrogance affect fraudulent financial reporting. This study used 51 financial reports from fraud companies indicated by the Financial Services Authority and 51 financial reports from other companies in similar industry, listed on the Indonesian Stock Exchange from 2009 to 2018. The proxies of fraud pentagon were tested by using the logistic regression. The results showed that pressure, opportunity and rationalization had significant effects on fraudulent financial reporting. Meanwhile, capability and arrogance have no effect. These results indicate that the existence of pressure and rationalization can lead to financial fraud, but opportunity negatively affect fraudulent financial reporting. The results of this study contribute to the development of accounting science and to provide information on the prevention and detection of fraud in companies.AbstrakFraud menyebabkan kerugian di dunia bisnis yang mencapai triliunan rupiah. Dengan bingkai fraud pentagon, penelitian ini bertujuan untuk menguji apakah pressure, opportunity, rationalization, capability dan arrogance mempengaruhi terjadinya kecurangan pada laporan keuangan. Penelitian ini menggunakan 51 laporan keuangan dari perusahaan yang terindikasi fraud dari Otoritas Jasa Keuangan dan 51 laporan keuangan dari perusahaan sejenis yang tercatat di Bursa Efek Indonesia sebagai pembanding mulai dari tahun 2009 hingga 2018. Hubungan antar variabel diuji dengan menggunakan regresi logistik. Hasil penelitian menunjukkan bahwa variabel pressure, opportunity, dan rationalization berpengaruh terhadap fraudulent financial reporting, sedangkan capability dan arrogance tidak berpengaruh terhadap fraudulent financial reporting. Hasil tersebut menunjukkan bahwa adanya pressure dan rationalization mendorong perusahaan melakukan kecurangan pada laporan keuangan, sedangkan opportunity berpengaruh negatif terhadap tindak kecurangan pada laporan keuangan. Hasil penelitian ini berkontribusi dalam pengembangan ilmu akuntansi serta untuk memberikan informasi mengenai pencegahan dan mendeteksi adanya fraud di perusahaan.